2019
DOI: 10.1155/2019/8507453
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Effect of Fenugreek Seed Powder Solution (Trigonella foenum-graecum L.) on Hyperlipidemia in Diabetic Patients

Abstract: Background. Many drugs are commercially available for use in the management of diabetes. However, their side effects and high costs underscore the need for herbal alternative drugs. Trigonella foenum-graecum is one of the medicinal plants which are important in the management of diabetes mellitus. This study investigated the effect of Trigonella foenum-graecum seed powder solution on the lipid profile of newly diagnosed type II diabetic patients. Methods. A total of N=114 newly diagnosed type II diabetic patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(100 citation statements)
references
References 21 publications
3
78
0
Order By: Relevance
“…In our meta‐analysis of 15 RCTs (11 with control and 4 without control; Abdel‐Barry et al, 2000; Chevassus et al, 2009; Fedacko et al, 2016; Gaddam et al, 2009; Geberemeskel et al, 2019; Gupta & Gupta, 2001; Kandhare et al, 2018; Kassaian et al, 2009; Kumar et al, 2015; Maheshwari et al, 2017; Moosa et al, 2006; Najdi et al, 2019; Rafraf et al, 2014; Sfar et al, 2018; Yousefi et al, 2017), intake of fenugreek resulted in a significant reduction in TC, TG, and LDL only in studies with control but not in uncontrolled studies. Our results showed that fenugreek consumption has significant positive effect on HDL elevation both in controlled and uncontrolled studies.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…In our meta‐analysis of 15 RCTs (11 with control and 4 without control; Abdel‐Barry et al, 2000; Chevassus et al, 2009; Fedacko et al, 2016; Gaddam et al, 2009; Geberemeskel et al, 2019; Gupta & Gupta, 2001; Kandhare et al, 2018; Kassaian et al, 2009; Kumar et al, 2015; Maheshwari et al, 2017; Moosa et al, 2006; Najdi et al, 2019; Rafraf et al, 2014; Sfar et al, 2018; Yousefi et al, 2017), intake of fenugreek resulted in a significant reduction in TC, TG, and LDL only in studies with control but not in uncontrolled studies. Our results showed that fenugreek consumption has significant positive effect on HDL elevation both in controlled and uncontrolled studies.…”
Section: Discussionmentioning
confidence: 82%
“…Two articles one in Chinese (Shen, Li, Lu, Yu, & Zheng, 2013) and one published before 2000 (Bordia, Verma, & Srivastava, 1997) which did not meet our inclusion criteria were excluded. Finally only 15 articles were selected for meta‐analysis (11 controlled and four uncontrolled; Abdel‐Barry, Abdel‐Hassan, Jawad, & al‐Hakiem, 2000; Chevassus et al, 2009; Fedacko et al, 2016; Gaddam et al, 2009; Geberemeskel, Debebe, & Nguse, 2019; Gupta & Gupta, 2001; Kandhare, Phadke, Mane, Thakurdesai, & Bhaskaran, 2018; Kassaian, Azadbakht, Forghani, & Amini, 2009; Kumar, Kumar, Datta, & Bandyopadhyay, 2015; Maheshwari et al, 2017; Moosa et al, 2006; Najdi, Hagras, Kamel, & Magadmi, 2019; Rafraf, Malekiyan, Asghari‐Jafarabadi, & Aliasgarzadeh, 2014; Sfar et al, 2018; Yousefi et al, 2017) involving 281 cases consumed fenugreek and 255 control cases in controlled group and 136 cases in uncontrolled group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is not known exactly how its mechanism occurs, studies suggest that the seed may increase the excretion of bile. This causes the formation of large micelles, compromising the synthesis of triglycerides 10,11 .…”
Section: Medicinal Plants and Diabetesmentioning
confidence: 99%